Internal Control As A Mediator Of Audit Quality - Oyong Lisa; Umi Muawanah; Heriyadi Heriyadi; Ahmad Dahlan (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: The aim of this research is to analyze the influence of internal control on audit quality, examine the impact of integrity on internal control, investigate the effect of time budget pressure on internal control, assess the influence of integrity on audit quality through internal control, and explore the impact of time budget pressure on audit quality through internal control Methodology/approach: This study adopts an explanatory research approach, which aims to explain the relationships between the variables under investigation. The research sample consists of 72 auditors working in Public Accounting Firms in Surabaya, selected through purposive sampling based on predefined criteria. Primary data was collected using questionnaires distributed through the Google Form platform. After data collection, the analysis was conducted using the Smart PLS method, a statistical analysis approach used to test the structural model and relationships between research variables. Findings: The results of this study confirm that internal control has a significant impact on audit quality. Integrity significantly influences internal control, and time budget pressure also has a significant impact on internal control. Internal control acts as a mediator, explaining the influence of integrity on audit quality, as well as the effect of time budget pressure on audit quality Practical implications: The practical implications of this research encompass auditor training, audit planning, enhancement of internal controls, risk assessment, communication, continuous improvement, reporting, and future research directions in the field of auditing. These implications can be utilized by practitioners, audit firms, organizations, and researchers to elevate audit quality and foster ethical and effective audit practices. Originality/value: The originality and value of this research lies in a comprehensive examination of various factors in the context of auditing, particularly focusing on integrity, time budget pressures, internal controls, and their collective impact on audit quality. This in-depth analysis provides valuable insights for practitioners and researchers in the auditing field, offering practical implications for improving audit quality and promoting ethical auditing practices. In addition, this study introduces a mediation model that illustrates how internal control mediates the influence of integrity and time budget pressure on audit quality, contributing to a deeper understanding of the mechanisms underlying this relationship. Overall, the study's comprehensive approach, methodological rigor, and insightful findings contribute to advancing knowledge in auditing and providing actionable recommendations to improve auditing practice and results.